Sex work-related stigma: Experiential, symbolic and structural forms in the health systems of Delhi, India. (May 2019) - Ryan, Martha S.; Nambiar, Devaki; Ferguson, Laura
Abstract: Sex work-related stigma is prevalent in urban India. While HIV-stigma is often discussed in urban Indian health contexts, rarely is sex work-related stigma investigated as it shapes sex workers' health experiences. This paper discusses the findings of an ethnographic study with women who practice sex work (WPSW), healthcare providers, and NGO workers in Delhi, India over seven months in 2017. We apply a tri-tiered model of stigma as constituted of experiential, symbolic, and structural forms, to better understand how WPSW experience sex work-related stigma as it relates to their health. Identifying and understanding manifestations and experiences of stigma is crucial to supporting WPSW health. We conclude that in the face of criminalized legal contexts, both non-governmental and governmental interventions to improve WPSW's health must contend with their own tendencies to reinforce prevailing stereotypes and symbols that stigmatize sex work and the people who engage in it. Highlights: Sex work stigma shapes and constrains public health efforts directed at sex workers. Sex work stigma is only one layer of the many stigmas experienced by sex workers. Public health efforts to support sex workers must go beyond HIV.